Incidence of nuclei of fiscal accounting support in tax culture province of Chimborazo - Puente Riofrío, Mariana Isabel; Arias González, Iván Patricio; Álvaro Zurita, Verónica Paulina (mktDESCUBRE; Vol 1 No 18 (2021): Eighteenth Edition (July - December), 2021)
The tax culture is a fundamental component in every country, ignorance of the tax context constitutes a problem in the face of tax collection, the objective of this research was to analyze the incidence generated by the virtual modality of the Accounting and Tax Support Nuclei (NAF In Spanich) has generated in the tax culture of the province of Chimborazo. The type of research was mixed because quantitative and qualitative data were included, with a causal research scope, the study population represented the students of the admission and leveling coordination of the National University of Chimborazo, the Wilcoxon signed rank test was used to determine the incidence of the Nucleus of Accounting and Fiscal Support in the tax culture, the results obtained show an improvement in the tax culture after the intervention of the Nucleus of Accounting and Fiscal Support, of the National University of Chimborazo, therefore, it is concluded that there is an incidence of NAF in the tax culture.